A Study on effective factors to attract the private companies for official development assistance at the viewpoint of Public Private Partnership (PPP) - Ko, Mira (KDI School, 2011)
This research aims to find effective factors to attract the private companies to ODA and increase the scale of ODA fund for the developing countries. Therefore I compared CSR and PPP concept first. CSR is composed of the interaction between the company and society to make good results for both. PPP is the partnership with public and private sectors in order to make more efficiency and profits sharing risks. They have three similar factors such as the components, intends and contribution to society. I focused on the PPP for ODA in this research so I separated the issues more specifically. PPP for ODA is the action of the company which has cooperated with the public parts to contribute to developing countries. It is similar to CSR at the view point of good intentions and similar to PPP at the view point of risk sharing. So I should make the balance between CSR & PPP to find effective factors to attract the private companies for ODA field. Firstly, I analyzed the motivation for success of CSR and apply them to PPP for ODA. When the companies have altruism motivations, PPP in ODA should communicate its intentions to the public in a timely manner. In addition it is better to approach for positive impact not to reduce negative impact. Secondly in case of motivation of benefit intentions, company should choose the target of PPP which is not directly related to the main products. If the targets of PPP are very directly linked with the sales of the companies, consumers noticed the motivation for benefit easily and blamed its activities. Next in case of motivation for inside capabilities, they should take specific care for all parts of the company and manage its good reputation externally. Lastly in case of motivation for the risk management, time is very important. If it is late to respond against the risk, PPP programs get lost its objectives and make a negative impact. Then I made a survey to find effective factors to attrite the private companies specifically. People think working fields are not directly related to the interest of PPP but they prefer education field is the most related to PPP in ODA. In addition turnover of the companies are not related to the interest of PPP and previous CSR experience don't affect the motivation of the company to attract PPP positively. However people think the political stability is very important to PPP not the amount of fund from the public sector. Moreover they expect the public sector helps to improve the public relations and administration support and guarantee the security in developing countries. I researched the effective factors to attract the companies to PPP so I will collect best practices in real situation in the future. Even though the companies have attractive factors of PPP, they are afraid of new challenges without experiences. I will expect to research successful models in real situation.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: PPP--ODA--CSR